Integrated Exhaust System in Grossing Table for Formaldehyde Exposure Control - Meike Rachmawati; Wida Purbaningsih; Meta Maulida Damayanti; Iman Apriana Effendi; Faradilla Azzahra Dinariansyah; Fathin Azimati Nadila; Ismawati; Nugraha; Aninditya Putri Anugrah; Fattahrani; Reyiena Kusumaryani Rahmat (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Formaldehyde, a widely used tissue fixative in anatomical pathology laboratories, poses significant health risks due to its irritant and carcinogenic properties. Exposure control during grossing procedures is critical, yet commercial grossing tables with integrated ventilation systems are often cost-prohibitive. This study aimed to develop and evaluate a cost-effective grossing table equipped with a local exhaust ventilation system to reduce formaldehyde exposure in compliance with occupational health and safety (OHS) standards. A quasi-experimental study was conducted in collaboration with an anatomical pathology laboratory in Bandung, Indonesia, from 2023 to 2025, testing three exhaust configurations: (1) control (no exhaust), (2) room exhaust only (S1), and (3) room + table-mounted exhaust (S2). Session-level analysis using the Kruskal-Wallis test revealed significant differences among configurations (p=0.035). Post-hoc Mann-Whitney tests confirmed that exposure in S2 was significantly lower than in the control (p=0.024, 95% CI=0.25–0.70), indicating a large effect size. Mean session exposures decreased from control (0.86–1.50 ppm) to S1 (0.74–0.85 ppm) and S2 (0.58–0.62 ppm). The corresponding 8-hour time-weighted averages (TWA) were 0.403 ppm (control), 0.257 ppm (S1), and 0.086 ppm (S2), compared to the limits of 0.75 ppm (OSHA), 0.1 ppm (ACGIH), and 0.016 ppm (NIOSH). Short-term exposure limits (STELs) were 1.55 ppm, 1.11 ppm, and 0.29 ppm, benchmarked against two ppm (OSHA), 0.3 ppm (ACGIH), and 0.1 ppm (NIOSH), respectively. In conclusion, the S2 setup met OSHA and ACGIH limits, demonstrating that integrated local exhaust effectively reduces formaldehyde exposure and provides an effective engineering control to improve occupational safety in pathology laboratories. This low-cost intervention offers a practical solution for safer working conditions in pathology laboratories.